1975
DOI: 10.1172/jci107965
|View full text |Cite
|
Sign up to set email alerts
|

Bence Jones proteins and light chains of immunoglobulins. XI. A transient Bence Jones-related protein associated with corticosteroid therapy.

Abstract: A B S T R A C T Urine specimens from patients with multiple myeloma and Bence Jones proteinuria frequently contain low molecular weight proteins which correspond either to the amino-terminal, variant half (VL) Biosynthetic studies were performed with plasma cells derived from the bone marrow of this patient at a time when both the CL* and the Bence Jones protein were being excreted; both proteins were identified in extracellular culture fluid by immunochemical techniques. Whether the CL* is of synthetic or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…6 We have found that 6 A receptor protein of high affinity and specificity for the corticosteroid dexamethasone has been demonstrated in plasma cells from the established X Bence Jones protein-synthesizing plasma cell tumor line of patient KIR (see Results) contain receptor protein of high binding affinity for dexamethasone;7 it remains to be established whether the observed differences in the effect of corticosteroids on Bence Jones protein or immunoglobulin synthesis (5-7) reflect quantitative or qualitative differences in glucocorticoid-receptor proteins among clones of plasma cells. The formation of CL* components, noted in three patients, may signify yet another effect of the putative corticosteroid-receptor protein complex on transcription of plasma cell messenger RNA, although a catabolic origin of these proteins cannot be excluded (8). Because the concentrations of prednisone used in the biosynthetic studies were several orders of magnitude greater than that required in other systems for controlling protein synthesis via receptor complexing and transcriptional control, the corticosteroid-associated alterations of Bence Jones protein synthesis may have resulted from other known biochemical effects of corticosteroids, e.g., on lysosomal and other membranes (1).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…6 We have found that 6 A receptor protein of high affinity and specificity for the corticosteroid dexamethasone has been demonstrated in plasma cells from the established X Bence Jones protein-synthesizing plasma cell tumor line of patient KIR (see Results) contain receptor protein of high binding affinity for dexamethasone;7 it remains to be established whether the observed differences in the effect of corticosteroids on Bence Jones protein or immunoglobulin synthesis (5-7) reflect quantitative or qualitative differences in glucocorticoid-receptor proteins among clones of plasma cells. The formation of CL* components, noted in three patients, may signify yet another effect of the putative corticosteroid-receptor protein complex on transcription of plasma cell messenger RNA, although a catabolic origin of these proteins cannot be excluded (8). Because the concentrations of prednisone used in the biosynthetic studies were several orders of magnitude greater than that required in other systems for controlling protein synthesis via receptor complexing and transcriptional control, the corticosteroid-associated alterations of Bence Jones protein synthesis may have resulted from other known biochemical effects of corticosteroids, e.g., on lysosomal and other membranes (1).…”
Section: Introductionmentioning
confidence: 92%
“…This component was detected by immunoelectrophoretic analysis 5 days after treatment was initiated (Fig. 6B); it increased in concentration by day 7, and could not be detected 24 The amino-terminus of CL* from patient EDW differed from those of CL* from patients WMS and OAK which corresponded to positions 92 and 97/106, respectively, of the K light polypeptide chain (8 (20,21). However, it seems unlikely that the marked decrease in Bence Jones proteinuria associated with chemotherapy resulted from an increased catabolic rate or a decreased proteinuric rate.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Undiluted samples also were examined in similar fashion, as were unconcentrated urine specimens and 24-hour collections that had been dialyzed extensively against distilled water, lyophilized, and reconstituted to a protein concentration of 100 mg/mL. 10 …”
Section: Study Design Protein Analysesmentioning
confidence: 99%